Global invasibility potential of the shrub Baccharis drancunculifolia - Olivares-Pinto, Ulises; Barbosa, Newton P. U.; Fernandes, Geraldo Wilson (Revista brasileira de botânica, 2022)
The genus Baccharis (Asteraceae) comprises over 440 species distributed along North and South America. Some species of this genus have remarkable invasiveness, and one of these species is the South American shrub Baccharis dracunculifolia DC . Most of the introductions of non-indigenous species are held indirectly through trade, so it is believed that this species could become invasive worldwide with a particular interest in the North American continent because of the increasing sale of products derived from honey to this continent. The resin extracted from B. dracunculifolia is the leading source for preparing the green propolis produced in Southeastern Brazil. Thus, the main objective of this work is to apply an approach based on distribution modeling to investigate possible areas of high environmental suitability for B. dracunculifolia in the North American continent and the potential to the entire globe using current and two future scenaries. Our results show many areas of environmental suitability for B. dracunculifolia. This species can invade over 33 countries distributed into five continents, including North America, some of the most critical parts of the southern USA, and large areas in Mexico. Since the best way of countering biological invasions is prevention, we propose that the introduction of this species should be monitored.